2015
DOI: 10.1002/jor.22824
|View full text |Cite
|
Sign up to set email alerts
|

Ten weeks of treadmill running decreases stiffness and increases collagen turnover in tendons of old mice

Abstract: Increased tendon stiffness in response to mechanical loading is well established in young animals. Given that tendons stiffen with aging, we aimed to determine the effect of increased loading on tendons of old animals. We subjected 28-month-old mice to 10 weeks of uphill treadmill running; sedentary 8-and 28-month-old mice served as controls. Following training, plantaris tendon stiffness and modulus were reduced by approximately half, such that the values were not different from those of tendons from adult se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
30
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 36 publications
8
30
0
3
Order By: Relevance
“…Calcification, which is minimal in adult tendons, increases significantly with age. However, mechanical loading significantly reduces Achilles tendon calcification in old mice following exercise . The findings of this study indicate that age‐related changes in tendon can be modified with mechanical loading; they also reaffirm that even tendons from old animals are capable of replacing damaged and dysfunctional components of ECM to match with that of adult.…”
Section: Mechanobiological Responses In Aging Tendonssupporting
confidence: 63%
See 2 more Smart Citations
“…Calcification, which is minimal in adult tendons, increases significantly with age. However, mechanical loading significantly reduces Achilles tendon calcification in old mice following exercise . The findings of this study indicate that age‐related changes in tendon can be modified with mechanical loading; they also reaffirm that even tendons from old animals are capable of replacing damaged and dysfunctional components of ECM to match with that of adult.…”
Section: Mechanobiological Responses In Aging Tendonssupporting
confidence: 63%
“…In addition, MTR significantly increases the expression of stem cell markers, tenocyte genes, and down regulates non‐tenocyte related genes. A recent study subjected 28‐month‐old mice to 10 weeks of MTR (13 m/min, 6° incline, 30 min/day, 5 days/week); sedentary 8‐ and 28‐month‐old mice served as controls . The gene expression analysis from Achilles tendons of trained aging rats shows that Col1a1 and MMP8, which were decreased due to aging are restored to the same levels as that of adult mice after training.…”
Section: Mechanobiological Responses In Aging Tendonsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been shown that changes at the interfascicular matrix is an important factor to consider in the pathogenesis of tendinopathy [36]. With respect to pathogenesis and the effects of ageing and loading, other research has shown that ageing leads to changes in the tendon morphology and mechanics [37] with increase in non-enzymatic crosslinks and as a consequence an expected increase in stiffness [38]. However, stiffness seems to decrease as we age [39].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, mechanical loading can regulate the expression of several growth factors capable of stimulating collagen synthesis, such as TGF-b1, CTGF, and IGF-1 (31), which, in turn, increases type I and III collagen synthesis in peritendinous connective tissue in both human and rat tendons (14,32). In response to exercise, the tendons of old animals are capable of replacing damaged and dysfunctional components of ECM with tissue that is mechanically and structurally comparable to adult tissue (33). However, after treadmill running, the amount of lipid deposits decreased, and small amounts of proteoglycans and calcium sites remained in the patellar tendons of mice (23).…”
mentioning
confidence: 99%